2015
DOI: 10.1002/jmv.24441
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr and cytomegalovirus DNA salivary shedding correlate with long‐term plasma HIV RNA detection in HIV‐infected men who have sex with men

Abstract: The aim of the study was to evaluate cytomegalovirus (CMV) and Epstein-Barr virus (EBV) DNA salivary shedding in HIV-positive men who have sex with men (MSM) and to determine whether viro-immunological parameters and long-term (24 months) plasma HIV RNA (pHIV) detection may predict herpesviruses replication. A total of 193 HIV-positive MSM were consecutively recruited (mean CD4+ cell count 607 cells/mm(3) and mean nadir value 333 cells/mm(3) ); pHIV was analyzed for 24 months prior to saliva sampling: patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 39 publications
2
12
0
2
Order By: Relevance
“…The most frequent virological pattern detected in the same patients at both T0 and T1 was the isolated EBV DNA shedding, with a comparable frequency in SSPs and in DV; this result is in accord with our previous data [20]. EBV persists as a latent infection of a memory B cell population, and these cells recirculate between the blood and the lymphoid tissues; lytic infection in the oropharyngeal epithelium leads to oral shedding when reactivation occurs [33], whereas CMV persists as a latent infection of the myeloid lineage, and it can reactivate to lytic infection at various sites [34].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The most frequent virological pattern detected in the same patients at both T0 and T1 was the isolated EBV DNA shedding, with a comparable frequency in SSPs and in DV; this result is in accord with our previous data [20]. EBV persists as a latent infection of a memory B cell population, and these cells recirculate between the blood and the lymphoid tissues; lytic infection in the oropharyngeal epithelium leads to oral shedding when reactivation occurs [33], whereas CMV persists as a latent infection of the myeloid lineage, and it can reactivate to lytic infection at various sites [34].…”
Section: Discussionsupporting
confidence: 92%
“…Herpesvirus salivary shedding was not identified in 9 patients (9.8%, 7 SSPs and 2 PSPs); this last percentage is in accord with that reported in previous studies with a single herpesvirus salivary testing, ranging from 3 to 25% [17, 18, 20]. Conversely, we demonstrated multiple herpesvirus reactivations both at T0 and at T1 in 24 patients (26.1% of the overall study population).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The breakdown of the mucosal epithelial barrier by HIV may explain this association: Nazli et al [28] demonstrated that exposure to HIV-1 led to an upregulation of inflammatory cytokine production and to a significant decrease in tight junction protein expression and increased permeability while Tugizov et al [29] showed that tight junction disruption of the oral and anal epithelium due to the expression of the HIV tat and gp120 increased HPV pseudovirion paracellular penetration into the epithelium. However, we cannot exclude an independent role for immune-activation, as described for the interplay between HIV and CMV, EBV, and HHV-8 [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirms previous findings of asymptomatic herpesvirus replication in HIV-infected individuals who are suppressed on ART. [24, 41, 42] Although there was only a modest trend for higher mean shedding rates among HIV(+) participants compared to age-matched HIV(−) MSM, there are some significant findings among the HIV(+) group that will have important implications in further studies on HIV-herpesvirus co-infection. First, shedding rates at each of the four timepoints did not necessarily correlate with each other.…”
Section: Discussionmentioning
confidence: 99%